IT’S GOOD TO BE A TEACHER - Marshall, David G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1982)
What follows is not so light-hearted that it couldn’t happen. A Utopia for school principals, Marshall seems to say, is just over the horizon. And it follows, as the night the day, that having little left to do they then could really get in on the act and help their teachers. Would that be a Utopia for teachers? (Well, of course.) RÉSUMÉ Il faut faire bien attention de ne pas prendre ce qui suit trop à la légère. Selon Marshall, il semble que les directeurs d’école soient voués à devenir une simple utopie. Il s’ensuit que, n’ayant plus grand chose à faire, ils se mettent vraiment à l’oeuvre et aident leur corps enseignant. Parlerait-on alors d’utopie pour les professeurs? (Oui, bien entendu).